Examining the Impact of Argument Quality and Source Credibility on Consumers’ Behavioral Intention Toward Green Cosmetics : The Moderating Role of Perceived Innovativeness - Mathur, Smriti; Vishnoi, Sushant Kr.; Bagga, Teena; Mittal, Anand; Mittal, Arjun (Prabandhan: Indian Journal of Management, 2024)
Purpose : This study integrated the knowledge-attitude-behavior (KAB) model and the theory of planned behavior (TPB) to analyze how elements of electronic word of mouth (eWOM)—argument quality (AQ) and source credibility (CR)—influenced customers’ green cosmetics behavioral intention (BI). Methodology : Data were collected from a sample of 350 customers through an online survey, and a two-stage process was used to evaluate the research model. In the first stage, linear associations between the various elements of the theoretical model were determined using structural equation modeling (SEM). The second stage involved evaluating the predicting efficacy of the constructs, using an artificial neural network (ANN) framework. Findings : The findings of the multi-analytical study revealed that attitude (Atd), perceived behavioral control (Pbcon), and source credibility (CR) influenced consumers’ intentions to buy green cosmetics. Moreover, the source’s credibility (CR) and the argument’s quality (AQ) also positively influenced consumer attitude (Atd). The models appeared to have acceptable prediction accuracy based on the ANN study’s root mean square of error (RMSE) values. Originality : The study contributed to the body of green cosmetics literature by integrating knowledge-attitude-behavior (KAB) and planned behavior (TPB) theory. The novelty of this research also lies in examining the moderating effect of perceived innovativeness (PI) for developing a robust predictive framework for green cosmetics purchase intention using artificial neural networks (ANN).